Nudging fails to increase conservation actions among farmers - Correa, Miquel; Gsottbauer, Elisabeth; Nordén, Anna (Frontiers in Environmental Economics, 2025)
This paper presents findings from a randomized field experiment with over 7,200 Swedish farmers, evaluating the effectiveness of a behavioral nudge aimed at increasing engagement with a biodiversity conservation advisory service. The treatment group received a postcard featuring a peer farmer's testimonial and photo, highlighting the ease and benefits of adopting conservation practices. The control group received standard campaign materials from the national farming board. The intervention combined elements of salience, (peer) messenger effects, and social norms, but had no measurable effect on farmers' likelihood of requesting an advisory audit, the key first step toward participation in a new agri-environmental scheme. Exploratory subgroup analysis, however, reveals suggestive evidence that the nudge may have been more effective among female farmers and those already engaged in biodiversity efforts. Overall, these results suggest that behavioral nudges may have limited impact in promoting voluntary uptake of sustainable farming practices. Implications for the design of behavioral interventions in agricultural policy are discussed.